PENELITIAN EKSPERIMENTAL DALAM PEMBELAJARAN BAHASA KEDUA - Ratminingsih, Ni Made (Universitas Pendidikan Ganesha, 2010)
Experimental research is one of the main approaches in second language research.The main objective of this kind of research is to determine the cause and effect oftwo phenomena. This article discusses what an experimental research is, kinds ofdesigns in experimental research, the use of experimental research in the secondlanguage instruction, and strengths and weaknesses of experimental research.Key words: experimental research, second language, design